THE EFFECTIVENESS OF MULTIMEDIA IN TEACHING SIMPLE PRESENT TENSE FOR THE JUNIOR HIGH SCHOOL - Djoko Sri Bimo; Sri Murni; Maria Yustina Rensi Dartani (ETERNAL (English Teaching Journal), 2021)
The use of multimedia technologies in education has enabled teachers to simulate final outcomes and assist students in applying knowledge learned from textbooks, thereby compensating for the deficiency of traditional teaching methods. It is important to examine how effective the technologies are in practical use. The purpose of the study was to describe the implementation of interactive multimedia and to describe the level of defiance of the eighth grade students of SMP Muhammadiyah 1 Surakarta in learning of Simple Present Tense.  The study utilized a teaching experiment with a non-equivalent pretest-posttest experimental group design to test and discuss students’ professional cognition, operating skill cognition, and level of learning achievement during the learning process. No significant differences emerged between the groups in regards to professional cognition or operation skills cognition. However, a significant difference in learning achievement was noted, indicating that the treatment with multimedia produced greater achievement than with traditional learning methods. Results are explained in detail and recommendations for further research provided. The result showed that teaching learning process by using multimedia is not only helping teacher in delivering the target language but also motivating the students in learning where it providesaudio and visual materials that make the students attract to the lesson and give more attention to it.